Prevalence and clinical profile of thyroid eye disease among patients with thyroid dysfunction visiting a tertiary care teaching hospital - Thapa Godar, Srijana; Bahadur Khattri, Jai; Raj Acharya, Ramesh (Journal of Chitwan Medical College, 2024)
Background: Thyroid eye disease (TED) is an autoimmune disease affecting ocular and orbital tissues. The objective of this study was to find out the prevalence of thyroid eye disease and the prevalence of different clinical profile of thyroid eye disease in patients with thyroid dysfunction.Method: This was a hospital based cross-sectional study conducted among 93 patients with thyroid dysfunction of aged 30 years and above. Standard proforma was used to collect socio-demographic and clinical variables of the patients. Detailed ocular examination was done to assess thyroid eye disease. The statistical methods used were mean, frequency and percentage.Result: The prevalence of thyroid eye disease was 47.31%. Thyroid eye disease was more prevalent in female (77.27%) and in hypothyroid (50.0%). Among patients with thyroid eye disease, 15.91% had history of smoking, 34.09% had family history and 47.73% had the duration of thyroid dysfunction of more than 48 months. The commonest symptom was foreign body sensation (59.09%), dry eyes (54.55%), discomfort of eyes (52.27%) and prominent eyes (50%). Lid lag (81.81%) was the commonest sign followed by lid retraction (70.45%), proptosis (56.82%) and conjunctival congestion (52.27%).Conclusion: There was a high prevalence of thyroid eye disease among the thyroid dysfunction patients. Foreign body sensation, dry eyes, prominent eyes are common symptoms whereas lid lag, lid retraction, proptosis are the common signs of thyroid eye disease.